1984
DOI: 10.1128/jvi.51.2.329-339.1984
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of adeno-associated virus: isolation and preliminary characterization of adeno-associated virus type 2 mutants

Abstract: We constructed insertion and deletion mutants with mutations within the adeno-associated virus (AAV) sequences of the infectious recombinant plasmid pSM620. Studies of these mutants revealed at least three AAV phenotypes. Mutants with mutations between 11 and 42 map units were partially or completely defective for rescue and replication of the AAV sequences from the recombinant plasmids (rep mutants). The mutants could be complemented by mutants with replication-positive phenotypes. The protein(s) that is affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
186
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(196 citation statements)
references
References 65 publications
8
186
2
Order By: Relevance
“…This study directly demonstrates that AAV Rep78 forms homo-multimers by both West-Western and chemical crosslinking analysis. We believe that this self recognition is to be expected due to Rep78's multiple roles in transcriptional regulation [7-15] and DNA replication [3,4]. Rep78's interaction with DNA has been studied extensively [6,16,17,[28][29][30][31][32], but its potential protein-protein interactions have not.…”
Section: The Rep78 Protein Binds To Specific Nuclear Proteins Presentmentioning
confidence: 99%
See 1 more Smart Citation
“…This study directly demonstrates that AAV Rep78 forms homo-multimers by both West-Western and chemical crosslinking analysis. We believe that this self recognition is to be expected due to Rep78's multiple roles in transcriptional regulation [7-15] and DNA replication [3,4]. Rep78's interaction with DNA has been studied extensively [6,16,17,[28][29][30][31][32], but its potential protein-protein interactions have not.…”
Section: The Rep78 Protein Binds To Specific Nuclear Proteins Presentmentioning
confidence: 99%
“…Adeno-associated virus (AAV) is a helper dependent human parvovirus, which requires that the cell be co-infected with an adeno-or herpes virus to allow for AAV productive infection [1,2]. The Rep78 nuclear protein, encoded by AAV, plays important roles in AAV DNA replication [3,4], AAV chromosomal DNA integration into human chromosome 19 [5,6], the irans-regulation of AAV gene expression [7][8][9], and the /raniregulation of various heterologous genes [10][11][12][13][14][15]. Consistent with Rep78's many biological roles it has many defined biochemical activities.…”
Section: Introductionmentioning
confidence: 99%
“…These systems have advanced the structural studies of the AAV capsid as a result of the large amount of empty capsids or virus-like particles (VLPs) that can be produced. Studies of AAV assembly have demonstrated that VP3 alone is sufficient to form VLPs [26], but VP1 is required for infectivity [27]. Subsequently, it was shown that the unique N-terminus of VP1 has phospholipase A2 activity and contains a nuclear localization signal (NLS) [28].…”
Section: Introductionmentioning
confidence: 99%
“…Rep78/68 are required to regulate transcription from all three promoters and to replicate the viral DNA. 10,11) Furthermore, Rep78/68 are also involved in the preferential integration of AAV genomes into the AAVS1 locus. 12) Spliced and unspliced transcripts from the p19 promoter encode Rep40 and Rep52, respectively.…”
mentioning
confidence: 99%